MENTAL HEALTH OUTCOMES AMONG FLOOD-PRONE COMMUNITIES: A CROSS-SECTIONAL ANALYSIS OF DEPRESSION AND ANXIETY IN SELANGOR, MALAYSIA - Sulaini, Nor Hafazan; Mokhtar, Siti Aisah (Malaysian Journal of Public Health Medicine, 2025)
Anxiety and depressive disorders are prevalent mental health issues globally. Its incidence can be significantly influenced by floods, the most frequent natural disaster. This study aimed to determine the prevalence of depression and anxiety and identify associated factors among adults residing in flood-prone areas in Klang, Selangor, Malaysia. A cross-sectional study was conducted among 339 adults aged 18 and above selected through stratified proportionate sampling. Depression and anxiety were assessed using the Patient Health Questionnaire and Generalized Anxiety Disorder scales. Data were analysed using IBM SPSS software version 29 to determine the association between variables using Chi-square or Fisher’s Exact test. Meanwhile, predictors of depression and anxiety were analysed using multiple logistic regression. The prevalence of depression and anxiety were 8.0% (n=27) and 12.4% (n=42) respectively. Significant predictors for depression were younger adults (18 to 29) (aOR 4.458, 95% CI 1.100, 18.063, p<.05) and low resilience (aOR 4.577, 95% CI 1.796, 11.666, p<.05), while anxiety predictors included younger adults (18 to 29) (aOR 7.770, 95% CI 1.562, 38.653, p<.05), being self-employed (aOR 0.291, 95% CI 0.102, 0.827, p<.05, affected financial status (aOR 3.725, 95% CI 1.194, 11.625, p<.05) and low resilience (aOR 3.934, 95% CI 1.567, 9.875, p<.05). These findings demonstrate the need for targeted interventions to enhance resilience, particularly among younger adults to mitigate these mental health outcomes.